The use of the Eurosystem's monetary policy instruments and operational framework since 2012 - Inmaculada Alvarez; Fabio Casavecchia; Marino De Luca; Alexander Duering; Fabian Eser; Caspar Helmus; Christophe Hemous; Niko Herrala; Julija Jakovicka; Michelina Lo Russo; Filippo Pasqualone; Marc Rubens; et al. (European Central Bank (ECB), 2017)
This paper provides a comprehensive overview of the use of the Eurosystem's monetary policy instruments and the operational framework from the third quarter of 2012 until the first quarter of 2016. The paper reviews the context of Eurosystem market operations, counterparty and collateral framework, participation in tender operations, recourse to standing facilities, patterns of reserve fulfilment, outright asset purchase programmes, as well as the impact of the ECB's monetary policy implementation on the Eurosystem's balance sheet and liquidity conditions.
Keywords: D02; E43; E58; E65; G01; 330; Monetary policy implementation; Central bank operational framework; Central bank liquidity management; Non-standard monetary policy measures